Trends in the association between educational assortative mating, infant and child mortality in Nigeria - Tolulope Ariyo; Quanbao Jiang (BMC, 2021)
Abstract Background Existing knowledge has established the connection between maternal education and child survival, but little is known about how educational assortative mating (EAM), relates to childhood mortality. We attempt to examine this association in the context of Nigeria. Methods Data was obtained from the 2008, 2013, and 2018 waves of the Nigeria Demographic and Health Survey, which is a cross-sectional study. The sample includes the analysis of 72,527 newborns within the 5 years preceding each survey. The dependent variables include the risk of a newborn dying before 12 months of age (infant mortality), or between the age of 12-59 months (child mortality). From the perspective of the mother, the independent variable, EAM, includes four categories (high-education homogamy, low-education homogamy, hypergamy, and hypogamy). The Cox proportional hazard regression was employed for multivariate analyses, while the estimation of mortality rates across the spectrum of EAM was obtained through the synthetic cohort technique. Results The risk of childhood mortality varied across the spectrum of EAM and was particularly lowest among those with high-education homogamy. Compared to children of mothers in low-education homogamy, children of mothers in high-education homogamy had 25, 31 to 19% significantly less likelihood of infant mortality, and 34, 41, and 57% significantly less likelihood of child mortality in 2008, 2013 and 2018 survey data, respectively. Also, compared to children of mothers in hypergamy, children of mothers in hypogamous unions had 20, 12, and 11% less likelihood of infant mortality, and 27, 36, and 1% less likelihood of child mortality across 2008, 2013 and 2018 surveys, respectively, although not significant at p < 0.05. Both infant and child mortality rates were highest in low-education homogamy, as expected, lowest in high-education homogamy, and lower in hypogamy than in hypergamy. Furthermore, the trends in the rate declined between 2008 and 2018, and were higher in 2018 than in 2013. Conclusion This indicates that, beyond the absolute level of education, the similarities or dissimilarities in partners' education may have consequences for child survival, alluding to the family system theory. Future studies could investigate how this association varies when marital status is put into consideration.